Sehgal index and its comparison with Mentzer’s index and Green and King index in assessment of peripheral blood smear with marked anisopoikilocytosis - Rastogi, Naincy; Bhake, Arvind S. (International Journal of Research in Medical Sciences, 2020)
Background: Mild microcytic hypochromic anaemias due to iron deficiency (IDA) and beta thalassemia trait(β-TT) continue to be a cause of significant burden to the society, particularly in the poorer developing countries. The objective of the present study was to study the RBC based indices in patients of marked anisopoikilocytosis in determining the etiology of it, to standardize few automated red cell parameters, and also objective grading of RBC morphology on peripheral smear and interpreting its utility in indicating a diagnosis. Also, to establish a relation between value of RBC indices with that of degree of anisocytosis. Methods: A total of 500 patients diagnosed with mild microcytic hypochromic anaemia on complete blood count and peripheral blood film were included in the study. Hb, RBC count, MCV, MCH and RDW obtained from the electronic cell counter were used to calculate discrimination indices by various mathematical formulae. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and Youden’s index (YI) were calculated. Results: Green and King index demonstrated the lowest sensitivity of 70.51%. Mentzer index demonstrated the highest specificity of 96.80%. The highest and lowest PPV were found for Mentzer index (97.09%) and Sehgal index (92.81%) respectively. Sehgal’s index demonstrated the highest NPV of 95.96% and lowest NPV was exhibited by G and K (87.9%). The highest and the lowest values for Youden’s index were shown by Sehgal’s index (87.82%) and G and K index (68.47%). Conclusions: Sehgal’s index followed by Mentzer index are highly sensitive and reasonably specific in differentiating β-TT from IDA and none of the indices is 100% sensitive and specific. Though HbA2 estimation is the gold standard for diagnosing β-TT, in developing countries, Sehgal index followed by Mentzer et al, index can be used to screen mild microcytic hypochromic anaemia cases to eliminate as many false positive cases as possible to reduce the financial cost.